A cost-effectiveness and budget impact analysis of apremilast in patients with psoriasis in the Italian setting. (2nd April 2020) - Barbieri, Marco; Loconsole, F.; Migliore, A.; Capri, S.
Abstract: Aims: The aim of this study was to conduct a cost-effectiveness analysis, as well as a budget impact analysis, on the use of apremilast for the treatment of adult patients with moderate-to-severe plaque psoriasis (defined as a psoriasis area severity index [PASI] ≥ 10), who failed to respond to, had a contraindication to, or were intolerant to other systemic therapies, within the Italian National Health Service (NHS). Materials and methods: A Markov state-transition cohort model adapted to the Italian context was used to compare the costs of the currently available treatments and of the patients' quality of life with two alternative treatment sequences, with or without apremilast as pre-biologic therapy. Moreover, a budget impact model was developed based on the population of patients treated for psoriasis in Italy, who would be eligible for treatment with apremilast. Results: Over 5 years, the cost-effectiveness analysis showed that the strategy of using apremilast before biologic therapy was dominant compared with the sequence of biologic treatments without apremilast. In addition, it is important to underline that the use of apremilast slightly increases the quality-adjusted life years gained over 5 years. Furthermore, within the budget impact analysis, the strategy including apremilast would lead to a saving of €16 million within 3 years. Savings would mainly be related to a reduction in pharmaceutical spending, hospital admissions and other drug administration-related costs. Conclusion: These models proved to be robust to variation in parameters and it suggested that the use of apremilast would lead to savings to the Italian healthcare system with potential benefits in terms of patients' quality of life.